2016
DOI: 10.1037/abn0000199
|View full text |Cite
|
Sign up to set email alerts
|

Interaction takes two: Typical adults exhibit mind-blindness towards those with autism spectrum disorder.

Abstract: Recent work suggests that we are better at interpreting the movements of others who move like us, and that individuals with Autism Spectrum Disorder (ASD) move in a quantifiably different way from typical individuals. Therefore, 'social impairments' exhibited by individuals with ASD may, at least in part, represent a failure by typical individuals to infer the correct mental states from the movements of those with ASD. To examine this possibility, individuals with ASD and typical adults manually directed two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
158
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 152 publications
(167 citation statements)
references
References 41 publications
9
158
0
Order By: Relevance
“…In accordance with our hypotheses and corroborating the findings of Edey et al [], Schwartz et al [], and McAleer et al [], analyses of accuracy (H1) and consistency (H2) of perception were comparable in ASD and TD. This suggests that social perception in ASD is intact.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with our hypotheses and corroborating the findings of Edey et al [], Schwartz et al [], and McAleer et al [], analyses of accuracy (H1) and consistency (H2) of perception were comparable in ASD and TD. This suggests that social perception in ASD is intact.…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, however, in both sensorimotor and imitation learning, we have found movement planning and execution differences between autistic and neurotypical controls. Others have also reported autism specific movement (i.e., increased variability in jerk) characteristics [Cook, ; Cook, Blakemore, & Press, ], which seem to influence the visual perception of observed actions [Brewer et al, ; Cook et al, ; Edey et al, ]. The implication is that a difference in autistic motor control could influence part of a predictive system that underpins social interaction in autism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results on pairs of NT participants [18, 44] instead showed no difference in coordination between same and opposite trials. Such an unexpected difference may be related to the fact that interaction is facilitated by within-group similarities in communication and interaction styles [45, 46], while interactions between out-group individuals may be more difficult [40]. Results on the difference in reaction times showed that when NT played adaptive, they always waited for their instructed partner to start his/her movement.…”
Section: Discussionmentioning
confidence: 99%